Abdullah ibn Rizvan-Pasha. The Chronicle «Tevarikh-i Desht-i Kiptchak». Part 1 - Refat Abduzhemilev (Крымское историческое обозрение)
The column presents one of the principal narrative sources reflecting the history of the Golden Horde and the Crimean Khanate – the work “Tevarikh-i Desht-i Kiptchak” (“The Chronicle of the Desht-i Kiptchak”, 1638) from under the pen of Abdullah ibn Rizvan. Notwithstanding the presence of works in the scientific literature on this chronicle, they still have a superficial character. The artistic and literary merits of the work have not been fully analyzed. The chronicle is a vivid example of the evolution of the Crimean and Ottoman traditions of verbal creativity and chronology, which later gave impetus to the emergence of other universal histories.